The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.15405/epsbs.2019.08.36
|View full text |Cite
|
Sign up to set email alerts
|

Understanding User Experience, Satisfaction, And Loyalty of Telecommunication Service Providers in Indonesia

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Noncommercial 4.0 Unported License, permitting all non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…Además de presentar las relaciones y los escenarios planteados entre los constructos, es estructurado por las construcciones teóricas de Maslach Burnout Inventory-Human Services Survey (MBI-HSS) (Maslach y Jackson, 1981), el Rapport (Gremler y Gwinner, 2000) y la escala COSE (Hennig-Thurau, 2004). Del mismo modo, para la experiencia del servicio o experiencia del cliente en la llamada telefónica (CX) propuesta por Jagodzi ński y Archer (2018), el modelo acogió el KPI operacional que la empresa objeto de estudio ha dedicado, a medir la relación Customer Satisfaction -Customer Experience (CallMiner, 2019;Rachmawati y Mohaidin, 2019;Colin, 2020).…”
Section: Descripción Del Modelo Propuestounclassified
“…Además de presentar las relaciones y los escenarios planteados entre los constructos, es estructurado por las construcciones teóricas de Maslach Burnout Inventory-Human Services Survey (MBI-HSS) (Maslach y Jackson, 1981), el Rapport (Gremler y Gwinner, 2000) y la escala COSE (Hennig-Thurau, 2004). Del mismo modo, para la experiencia del servicio o experiencia del cliente en la llamada telefónica (CX) propuesta por Jagodzi ński y Archer (2018), el modelo acogió el KPI operacional que la empresa objeto de estudio ha dedicado, a medir la relación Customer Satisfaction -Customer Experience (CallMiner, 2019;Rachmawati y Mohaidin, 2019;Colin, 2020).…”
Section: Descripción Del Modelo Propuestounclassified
“…Also, different authors have suggested that to improve the customer service department performance, reduce costs, unnecessary expenses and customer turn over, it is necessary to evaluate the customer experience construct and the customer's easiness to get a solution via Net Promoter Score (NPS) and Customer Effort Score (CES) (Dixon, Freeman & Toman, 2010;Koladycz, Fernandez, Gray & Marriott, 2018). Rachmawati & Mohaidin (2019) explain that the CSAT indicator searches to learn from the user´s emotions, perceptions, and expectations to afford satisfaction in the long term. On the other hand, if FCR and NPS are correctly managed, they can give access to higher levels of customer satisfaction while evaluating the experience acquired through the interaction with the contact center, resolutions reached in just one phone contact, percentage of customer loyalty and the customer's willingness to recommend services (Reichheld, 2003;Florea, Tănăsescu & Duică, 2018;Stanley, 2017).…”
Section: Call Center Key Performance Indicatorsmentioning
confidence: 99%
“…To boost and promote the interest of the public for using public transport, retaining the current customers, and at the same time gaining new users is one of the most practical methods [15]. Customer loyalty has become a key to measure the success of the businesses [16,17]. Besides that, customer satisfaction often makes its appearance in the context of customer loyalty as it is widely recognized that positive experiences lead to future behavior [18,19].…”
Section: Introductionmentioning
confidence: 99%